(untitled) (Latakia University Journal -Medical Sciences Series, 2023)
Breast cancer is a complex disease with different behaviors and responses to hormone therapy resistance. Inflammatory markers like IL-8 and CRP-hs are often elevated in breast cancer patients. This study aimed to characterize breast cancer subtypes and assess IL-8 and CRP-hs levels in patients at Tishreen-University Hospital in Syria from 2020 to 2022.The study included patients who had mastectomy with lymph node dissection, with an average age of 48.04±10.99 years. Results showed that the most common breast cancer subtypes were Luminal A1, TN, and TP. Older patients and those with Luminal B2 subtype had higher IL-8 and CRP-hs levels, but these differences were not statistically significant. There was a significant relationship between breast cancer subtypes and disease stage.In conclusion, most breast cancer patients in this study fell into Luminal A1, TN, and TP subtypes. The higher rate of negative ER-expression in Luminal B2 suggests a greater risk for hormone therapy resistance. Additionally, older patients with Luminal B2 subtype had higher IL-8 and CRP-hs levels. These findings enhance our understanding of breast cancer subtypes, their association with inflammatory markers, and hormone therapy resistance. Further research is needed to validate these results and explore potential therapeutic implications.